Factors affecting pregnancy outcomes in young women treated with fertility-preserving therapy for well-differentiated endometrial cancer or atypical endometrial hyperplasia. Issue 1 (December 2016) - Inoue, Osamu; Hamatani, Toshio; Susumu, Nobuyuki; Yamagami, Wataru; Ogawa, Seiji; Takemoto, Takashi; Hirasawa, Akira; Banno, Kouji; Kuji, Naoaki; Tanaka, Mamoru; Aoki, Daisuke
Abstract Background Patients hoping to preserve their fertility receive conservative treatment with high-dose medroxyprogesterone acetate (MPA) for well-differentiated endometrioid adenocarcinoma (EC) or atypical endometrial hyperplasia (AEH) . Such treatment generally involves frequent intrauterine operations, including dilation and curettage (D&C) and endometrial biopsy (EMB), which could result in endometritis, endometrial thinning, or intrauterine adhesion. In turn, any of these outcomes could adversely affect implantation and pregnancy development. The current study thus aimed to identify factors that might affect pregnancy following conservative treatment by MPA. Methods We compared a pregnancy group (45 patients) with a non-pregnancy group (53 patients) of MPA-treated patients to evaluate the factors affecting clinical pregnancy establishment. We undertook a multivariate logistic regression analysis based on factors shown by univariate analysis to be significantly different between the groups. Univariate analysis identified number of D&C, endometrial thickness, duration of MPA administration, age of pregnancy permission (the age at which a patient was first allowed to attempt pregnancy after disappearance of the lesion), period of disappearance of lesions, and recurrence as independent variables. Results The odds ratios (95 % confidence interval) of multivariate analysis for disease recurrence, endometrial thickness during ovulation, and age of pregnancy permission were 0.283 (0.102–0.785), 1.677 (1.251–2.248), and 0.889 (0.792–0.998), respectively. There was no significant difference in the other independent variables between groups. Conclusions We identified three factors considered to affect pregnancy establishment following conservative treatment with MPA: recurrence, endometrial thickness during ovulation, and the age of the pregnancy permission. Introduction of infertility treatment including assisted reproductive technology (ART) soon after achieving tumor disappearance by MPA would therefore be beneficial for patients with disease recurrence, thin endometrium, or a higher age of pregnancy permission.